Respons Pertumbuhan Bibit Kelapa Sawit dengan Aplikasi Pupuk Kompos Mucuna bracteata D.C dan ZPTAuksin NAA di Fase Prenursery - Pulungan, Nurliana; Zulfansyah, Ichpan (Jurnal Media Pertanian, 2025)
The application of mucuna bracteata D.C compost fertlizer and ZPT ( growth regulator) substances to oil palm seedlings alms to determine the effect of interaction between mucuna bracteata D.C fertilizer and ZPT NAA. The single effect of mucuna bracteata D.C fertilizer on the growht of oil palm seedlings in the pre-nursery phase this research was conducted in the experimental, Alwashliyah university from Nov 2024 to january 2025. This research was conducted using a randomized block Design (RAK) with a two- factor factorial pattern. And each combination was repeated 3 times. The fist factor is mucuna bracteata D.C fertilizer with four doses of 0  g 1 g 10 g and 15 g and a recommendatioon f 10 g. The second factor dose with four treatments of 0 gr 0,5 gr 1 gr and 1,5 gr observation variables such as growht . the parameters of this study were the percentage of plant life , length of ol palm stems, Number of leaves (strands) root length (cm) total wet weight of plants, total dry weight of plants. The results of the study showed that the higher the amount of Mucuna bracteata compost and  NAA Auxin ZPT given, the better growth of oil palm seedlings. This can be seen in the parameters of 100 % survival life, root length of 2,66 cm, number of leaves of 4.88 strands, root length of 3,75 cm, total wet weight of 4.65 g and dry weight of 2.41 g.